2022
DOI: 10.3389/fphys.2021.820251
|View full text |Cite
|
Sign up to set email alerts
|

Fat Quantification Imaging and Biophysical Modeling for Patient-Specific Forecasting of Microwave Ablation Therapy

Abstract: Computational tools are beginning to enable patient-specific surgical planning to localize and prescribe thermal dosing for liver cancer ablation therapy. Tissue-specific factors (e.g., tissue perfusion, material properties, disease state, etc.) have been found to affect ablative therapies, but current thermal dosing guidance practices do not account for these differences. Computational modeling of ablation procedures can integrate these sources of patient specificity to guide therapy planning and delivery. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 63 publications
(106 reference statements)
1
8
1
Order By: Relevance
“…After ~5 minutes, ablation volume trajectories in the enhanced digital twin models do have some distinction from the control models, but it is limited. Looking across disease states, higher fat content corresponds to larger ablations in both model types, a trend established in previous work [13]. To further illustrate the effects of fat content and heterogeneity on the ablation zone, the long-axis and short-axis diameters were calculated by fitting an ellipsoidal equation to the ablation zone at the end of the 15-minute ablation.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…After ~5 minutes, ablation volume trajectories in the enhanced digital twin models do have some distinction from the control models, but it is limited. Looking across disease states, higher fat content corresponds to larger ablations in both model types, a trend established in previous work [13]. To further illustrate the effects of fat content and heterogeneity on the ablation zone, the long-axis and short-axis diameters were calculated by fitting an ellipsoidal equation to the ablation zone at the end of the 15-minute ablation.…”
Section: Resultsmentioning
confidence: 63%
“…Modeling Framework: Patients' MR images were retrospectively reviewed by an experienced radiologist on one of two clinical scannersa clinical Philips Intera Achieva 3T MRI or a 1.5T Siemens Magnetom Sola MR scanner. The patient images, image sequences, and fat sampling methods to produce the homogenous digital twin models (control) are the same as those reported in previous work [13]. Figure 1 is the framework used in the study reported herein.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we proposed a computational framework to transform patient diagnostic and anatomical imaging data into a digital twin of thermal ablation with patient-specific but homogeneous tissue parameters [43] . The imaging data were used in two roles: to segment the liver parenchyma, and to sample the liver fat and map material properties using characteristic equations derived from prior work in mock tissue phantoms.…”
Section: Introductionmentioning
confidence: 99%